Ecological and epidemiological aspects of the spread of poultry red mite population (Environment & Health, 2017)
The objective of our work is to investigate the impact and spread of D. gallinae infestation on poultry enterprises in Ukraine and make analysis of data of the European Union which is the most common that blood-sucking parasite. Determine the action and value this ectoparasite.Materials and methods. The methodological basis of our research is general theoretic methods of scientific knowledge, systematically-structural and abstractly-logical analysis.Results The negative influence of Dermanyssus gallinae on the production of poultry products, and most of all, on the production of eggs is shown. In the EU countries, in recent decades, a high percentage of parasite spread has been detected due to its high adaptive properties, acaricide resistance, fast life cycle at high optimal temperatures, and the ability to exist for a long time without a power supply (up to 10 months). It is found out that a parasite can enter a poultry farm with synanthropic poultry. The ticks are able to tolerate pathogens of dangerous infections and viruses causing transmissible and invasive diseases. All this causes economic losses to poultry enterprises by increasing the stockbreeding deaths (weight loss and anemia) and a significant reduction in egg and egg quality in chickens. Relevant consequences will result in significant financial costs for parasite populations, disinfection of premises and animal treatment. It also shows the deleterious effects of D. gallinae and the human body that causes skin diseases (itching and dermatitis). Thus, it is necessary to investigate the population of ticks in order to prevent their attacks on the workers of the poultry farms and to solve the problem ecologically.
Keywords: bird red mite; transmissible diseases; invasive diseases; parasitism; human impact; ecological peculiarities